The role of common mycorrhizal networks for forest regeneration near clear-cut edges : implications for management - Björs, Marcus (SLU/Dept. of Forest Ecology and Management, 2022)
Poor regeneration close to edges on clear-cuts and around seed trees in the Swedish boreal zone is well-known to foresters. With an intensifying national and European discussion concerning forestry, the prominence of edge effects is likely to increase. However, little is known of the drivers behind these edge effects. Recent developments in the research surrounding ectomycorrhizal fungi and their ability to form common mycorrhizal networks may be able to explain some of these patterns. In this study, I have analysed growth data of Scots pine seedlings planted in a Chequered-Gap-Shelterwood-System trial located in Jämtland, Sweden. I found that growth is significantly higher in the centre of a clear-cut gap than in the edge zone, defined as within five metres from the clear-cut edge. Which side of the gap the plants were exposed to was also partially significant. The results correlate well with the expected outcomes of below-ground competition described in literature. These edge effects may have long term implications for management due to lower growth, but the usage of new management methods may bring positive social benefits.